Cell-to-Cell Adhesion and Electrical Parameters of Murine Embryo Membranes After Cryopreservation by Vitrification - Smolyaninova, Yevgeniya; Shigimaga, Victor; Popivnenko, Lyudmila; Kovalenko, Igor (Problems of Cryobiology and Cryomedicine, 2023)
In this work, we have studied the impact of various stages of cryopreservation by vitrification in ethylene glycolsucrose medium on plasma membranes adhesive properties of 8-cell murine embryos and their specific electrical conductivity. Embryos were divided into the following experimental groups: the control, group 1 (incubation in vitrification medium) and group 2 (complete cycle of cryopreservation). The embryo exposure to vitrification medium did not affect their ability to cell-to-cell adhesion. After a complete cycle of cryopreservation, no embryo adhesion was observed. Electrical conductivity of embryo membranes was determined using the pulsed conductometry. After incubation in vitrification medium, their resistance to electric pulse was shown to decrease, that was manifested in the phenomenon of irreversible electric breakdown. The average values of electrical conductivity varied within the following ranges: ((12.1 ± 1.5)...(55.5 ± 2.6)), ((28.7 ± 5.7)...(44.± 8.9)), ((31.0 ± 9.3)...(87.9 ± 26.1)) μS/cm in the control, groups 1 and 2, respectively. These findings may be explained by appearance of first structural disorders in lipid bilayer of embryo membranes even at the stage of their incubation in vitrification medium. The lack of adhesive properties of blastomeres after vitrification-warming testified to a damage to the membrane adhesion proteins. Probl Cryobiol Cryomed 2022; 32(4):256–266